The factors affecting women entrepreneurship in developing countries. How far are we from supporting women entrepreneurship? - Gafar Almhamad (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. This study was conducted in the coastal region of Syria during 2022, shedding the spotlight on a group of female entrepreneurs domiciled in the Latakian Chamber of Commerce and Industry. The study relied on a wide range of primary and secondary data to identify, ascertain, and define the factors embracing female entrepreneurship and the impact of the Syrian crisis on these factors. The purpose of the study is to examine the realistic status of women's entrepreneurial projects in Syria by focusing on their strengths and weaknesses of their energy utilization as an active force in achieving more economic growth. A qualitative research method was used to analyze the internal and external environment of entrepreneurship from the viewpoint of the participating female entrepreneurs. The primary results showed that the dissatisfaction and pressure factors are the main drivers towards women entrepreneurship in Syria, creating a space for creativity and stepping up out of the societal traditional norms. However, pressure economic factors such as poverty, lack of job opportunities and limited income possibilities are the most important reasons for incentivizing women to enter the leadership field and becoming entrepreneurs. The main challenges facing women entrepreneurs in Syria are the social traditions and norms, followed by the lack of management skills and the negative perception of society towards a working woman in addition to the absence of designed crafted training and entrepreneurial oriented education. Despite the Syrian government's adoption of entrepreneurial designed plans as one of the tools to empower women and enabling them to be financially productive therefore to reduce poverty, interest appears to be absent or generally weak on the practical level considering the lack of supporting means, funding lines or strategic planning views which all together made many of these projects and ideas to operate in an unstructured and an unofficial manner, carrying out their potential to an unknown path.

Резюме. Дане дослідження було проведено в прибережному регіоні Сирії протягом 2022 року, приділяючи увагу групі жінок-підприємців, які проживають у Торгово-промисловій палаті Латакії. Дослідження спиралося на широкий спектр первинних і вторинних даних, щоб ідентифікувати, з’ясувати та визначити чинники, що охоплюють жіноче підприємництво, і вплив сирійської кризи на ці фактори. Мета дослідження полягає в тому, щоб вивчити реалістичний статус жіночих підприємницьких проектів у Сирії, зосередивши увагу на їхніх сильних і слабких сторонах використання енергії як активної сили для досягнення більшого економічного зростання. Для аналізу внутрішнього та зовнішнього середовища підприємництва з точки зору жінок-підприємців було використано якісний метод дослідження. Основні результати показали, що фактори незадоволеності та тиску є основними рушійними силами жіночого підприємництва в Сирії, створюючи простір для творчості та виходячи з традиційних суспільних норм. Проте економічні чинники тиску, такі як бідність, відсутність можливостей роботи та обмежені можливості отримання доходу, є найважливішими причинами, які спонукають жінок вийти на сферу лідерства та стати підприємцями. Основними проблемами, з якими стикаються жінки-підприємці в Сирії, є соціальні традиції та норми, за якими слідує відсутність управлінських навичок і негативне сприйняття суспільства щодо працюючих жінок, а також відсутність спеціального навчання та освіти, орієнтованої на підприємництво. Незважаючи на прийняття сирійським урядом розроблених підприємницьких планів як одного з інструментів для розширення прав і можливостей жінок і надання їм можливості бути фінансово продуктивними, а отже, для зменшення бідності, однак, інтерес відсутній або загалом слабкий на практичному рівні, враховуючи відсутність засобів підтримки, ліній фінансування або погляди на стратегічне планування, які разом змусили багато з цих проектів та ідей діяти не структуровано та неофіційно, реалізуючи свій потенціал у невідомому шляху.

Ezt a tanulmányt Szíria tengerparti régiójában végezték 2022-ben, a Latakia Kereskedelmi és Iparkamarában élő női vállalkozók egy csoportjára összpontosítva. A tanulmány az elsődleges és másodlagos adatok széles körére támaszkodott, hogy azonosítsa, feltárja és számszerűsítse azokat a tényezőket, amelyek felölelik a nők vállalkozói szellemét, valamint a szíriai válság hatását ezekre a tényezőkre. A tanulmány célja, hogy megvizsgálja a női vállalkozói projektek reális helyzetét Szíriában, összpontosítva azokra az erősségekre és gyengeségekre, amelyek az energiát a nagyobb gazdasági növekedést elősegítő eszközként használják fel. Kvalitatív kutatási módszerrel elemeztük a vállalkozás belső és külső környezetét a női vállalkozók szemszögéből. A fő megállapítások azt mutatták, hogy az elégedetlenség és a nyomás tényezői a fő mozgatórugói a női vállalkozói szellemnek Szíriában, teret teremtve a kreativitásnak és elszakadva a hagyományos társadalmi mintáktól. Mindazonáltal az olyan gazdasági nyomás, mint a szegénység, a munkalehetőségek hiánya és a korlátozott bevételi lehetőségek a legfontosabb tényezők, amelyek arra késztetik a nőket, hogy vezető pozícióba lépjenek és vállalkozóvá váljanak. A szíriai női vállalkozók előtt álló fő kihívások a társadalmi hagyományok és normák, ezt követi a vezetői készségek hiánya és a dolgozó nők negatív társadalmi megítélése, valamint a vállalkozói szellemre összpontosító speciális képzés és oktatás hiánya. Annak ellenére, hogy a szír kormány elfogadta azokat az üzleti terveket, amelyeket a nők helyzetének megerősítése és pénzügyi termelékenységük lehetővé tétele, valamint a szegénység csökkentése egyik eszközeként dolgoztak ki, a támogatottság hiánya miatt azonban gyakorlatilag hiányzik az érdeklődés, vagy általában gyenge, amihez hozzájárul az eszközök hiánya, finanszírozási problámák vagy stratégiai tervezési perspektívák hiánya, amelyek együttesen sok ilyen projektet és ötletet arra kényszerítettek, hogy strukturálatlanul és illegálisan működjenek, ismeretlen módon valósítva meg a benne rejlő lehetőségeket.
Фактори, що впливають на жіноче підприємництво в країнах, що розвиваються. Наскільки ми далекі від підтримки жіночого підприємництва?
A női vállalkozói készséget befolyásoló tényezők a fejlődő országokban. Milyen messze vagyunk a női vállalkozások támogatásától?
https://aab-economics.kmf.uz.ua/aabe/issue/view/4
Keywords: Middle East; women; entrepreneurs; contribution to the economic growth; crisis